Analisis Faktor yang Mempengaruhi Anggota untuk Mengambil Keputusan Pembiayaan Murabahah : Studi Kasus: BMT Mentari Umat Wangon - Rakhmawati, Arri Maulida; Dianti, Ergita Rahma; Mafiroh, Ita Faikotul; Sulasih, Sulasih (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the factors influencing members’ decisions to take murabahah financing at BMT Mentari Umat Wangon. The research employed a quantitative approach with descriptive and verification methods. The population consisted of active members using murabahah financing, selected through purposive sampling. Independent variables included service quality, knowledge of Islamic products, trust, location, promotion, profit margin, and financing procedures, while the dependent variable was the members’ financing decision. Data were analyzed using multiple linear regression after validity, reliability, and classical assumption tests. The results show that service quality, Islamic product knowledge, trust, profit margin, and financing procedures significantly affect members’ decisions, whereas location and promotion have no significant effect. The most dominant factors are service quality and institutional trust. These findings support the Theory of Planned Behavior (TPB), which emphasizes that attitudes, trust, and perceived control are key determinants of financial decision-making. The study implies that BMT should enhance service quality, strengthen financial literacy related to Islamic products, and develop digital-based service systems to improve efficiency and competitiveness.